2021
DOI: 10.3390/app11125528
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Photovoltaic Generation in the Putumayo Department of Colombia

Abstract: The potential for generating electricity with photovoltaic systems is high in Colombia given its geographical position in the tropic. Some departments in Colombia have low electricity coverage and high rates. In the department of Putumayo there is a low coverage rate and high energy costs, while the solar radiation potential is high. Due to the geographical differences of the Putumayo subregions, the radiation potential for electricity generation is unknown. In addition, in this department the energy tariffs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The study suggests that renewable energy sources must be used efficiently to meet rising energy demands and reduce overall energy consumption. The results of the scientific studies showed that using renewable energy as a significant source of energy can reduce overall energy consumption and may provide a workable alternative for reducing the building's energy demand [1,2]. There is growing concern that the world is approaching a point where its energy resources will be depleted due to the rapid consumption of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…The study suggests that renewable energy sources must be used efficiently to meet rising energy demands and reduce overall energy consumption. The results of the scientific studies showed that using renewable energy as a significant source of energy can reduce overall energy consumption and may provide a workable alternative for reducing the building's energy demand [1,2]. There is growing concern that the world is approaching a point where its energy resources will be depleted due to the rapid consumption of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that a hybrid energy system including wind, photovoltaic, and diesel generators were the most economically feasible option and improved the voltage profile at the connection point. Moreover, numerous researchers have focused on solar PV systems' solar energy potential and viability as power generation sources in buildings, like hospitals, departments, and more [10][11][12][13][14][15][16][17]. For instance, Al-Najideen and Alrwashdeh [10] designed a 56.7 kW grid-connected PV system to cover the demand for electricity in the Faculty of Engineering at Mu'tah University in Jordan.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the proposed PV system produced 87% of the electricity needs of the building. Carlos et al [17] determined the practical potential for PV power generation in the Putumayo department of Colombia. They concluded that the PV system could cover the department's consumption by producing self-generating electricity and distributed generation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation